Epirubicin‐Loaded Superparamagnetic Iron‐Oxide Nanoparticles for Transdermal Delivery: Cancer Therapy by Circumventing the Skin Barrier. Issue 2 (13th June 2014) - Rao, Yue‐feng; Chen, Wei; Liang, Xing‐guang; Huang, Yong‐zhuo; Miao, Jing; Liu, Lin; Lou, Yan; Zhang, Xing‐guo; Wang, Ben; Tang, Rui‐kang; Chen, Zhong; Lu, Xiao‐yang
Abstract : The transdermal administration of chemotherapeutic agents is a persistent challenge for tumor treatments. A model anticancer agent, epirubicin (EPI), is attached to functionalized superparamagnetic iron‐oxide nanoparticles (SPION). The covalent modification of the SPION results in EPI–SPION, a potential drug delivery vector that uses magnetism for the targeted transdermal chemotherapy of skin tumors. The spherical EPI–SPION composite exhibits excellent magnetic responsiveness with a saturation magnetization intensity of 77.8 emu g −1 . They feature specific pH‐sensitive drug release, targeting the acidic microenvironment typical in common tumor tissues or endosomes/lysosomes. Cellular uptake studies using human keratinocyte HaCaT cells and melanoma WM266 cells demonstrate that SPION have good biocompatibility. After conjugation with EPI, the nanoparticles can inhibit WM266 cell proliferation; its inhibitory effect on tumor proliferation is determined to be dose‐dependent. In vitro transdermal studies demonstrate that the EPI–SPION composites can penetrate deep inside the skin driven by an external magnetic field. The magnetic‐field‐assisted SPION transdermal vector can circumvent the stratum corneum via follicular pathways. The study indicates the potential of a SPION‐based vector for feasible transdermal therapy of skin cancer. Abstract : As a novel transdermal anticancer agent, epirubicin‐loaded superparamagnetic iron oxide nanoparticles (EPI–SPION) exhibit excellent magnetic responsiveness, a pH‐sensitive release profile, and biocompatibility. The EPI–SPION composites, driven by magnetic force, can penetrate the human dermis stratum readily via a transfollicular pathway, which follows an alternative strategy for skin cancer treatment by using superparamagentic nanomaterials.